Relationship between raltegravir trough plasma concentration and virologic response and the impact of therapeutic drug monitoring during pregnancy. (March 2023) - Carvalho, Sabrina; Sheehan, Nancy L.; Valois, Silvie; Kakkar, Fatima; Boucher, Marc; Ferreira, Ema; Boucoiran, Isabelle
Background: Limited data is available on raltegravir (RAL) pharmacokinetics during pregnancy and the value of therapeutic drug monitoring (TDM) in pregnancy is unknown. This study aims to describe RAL trough plasma concentrations (Ctrough ) during pregnancy and review the impact of RAL TDM on outcomes. Methods: Women from the prospective mother-infant HIV cohort of Mother and Children's Infectious Diseases Center who received RAL during their pregnancy between 2011-2020 were included. TDM reports were reviewed and Ctrough values estimated when possible, using historical RAL half-lives. Results: We included 76 pregnant women of which 47 underwent TDM. We observed a significant association between virological response and Ctrough ( p -value .034) with an increase of 0.1 mg/L corresponding to a 2.96 reduction in the risk of having a detectable viral load. The results indicated that in pregnant women a RAL Ctrough threshold of 0.04 mg/L has a higher specificity (75%) as compared to our current Ctrough target value of 0.02 mg/L (25%) and an acceptable sensitivity (77%). No significant differences were observed between Ctrough at each trimester. When comparing pregnancies with and without TDM, no statistically significant differences were observed in the virologic response during pregnancy and at delivery, or with the need for triple antiretroviral prophylaxis in newborns. Conclusions: An association between RAL Ctrough and viral load was observed and achieving a RAL Ctrough of 0.04 mg/L or greater is a predictor of virologic response in pregnant women. The impact of TDM in pregnancy, however, could not be demonstrated.